2012
DOI: 10.1007/s13105-011-0143-x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of endogenous CO by ZnPP protects against stress-induced gastric lesion in adult male albino rats

Abstract: Carbon monoxide (CO) has been found to be produced in every living cell in a biochemical reaction catalyzed by heme-oxygenase (HO) enzyme which degrades heme into biliverdin, CO, and iron. Endogenous CO is not a waste product, but acts as a chemical messenger mediating and modulating many intracellular biochemical reactions that regulate physiological functions. This study was designed to investigate the effect of inhibition of endogenous CO production by zinc protoporphyrin (ZnPP), an HO inhibitor, on the gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 50 publications
1
3
2
Order By: Relevance
“…These conclusions were made despite the apparent inhibition of endogenous CO by ZnPP, while zinc has been shown to exert gastroprotective and anti-ulcer effects. This discrepancy between our results and their observation [ 42 ] may be due to different experimental conditions. Such difference include the combined method of stress induction with the use of pylorus ligating for assessment of gastric acid secretion and exposure to cold stress along with an experimental design, which included chronic (10 days) administration of this HO inhibitor [ 42 ] vs. the application of ZnPP in a single dose prior to stress exposure in our present work.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…These conclusions were made despite the apparent inhibition of endogenous CO by ZnPP, while zinc has been shown to exert gastroprotective and anti-ulcer effects. This discrepancy between our results and their observation [ 42 ] may be due to different experimental conditions. Such difference include the combined method of stress induction with the use of pylorus ligating for assessment of gastric acid secretion and exposure to cold stress along with an experimental design, which included chronic (10 days) administration of this HO inhibitor [ 42 ] vs. the application of ZnPP in a single dose prior to stress exposure in our present work.…”
Section: Discussioncontrasting
confidence: 99%
“…further enhanced this effect in gastric mucosa compromised by WRS. Similarly to our results, both Morsy et al and Ibrahim et al reported an increase in gastric HO-1 expression in response to cold stress as determined by immunohistochemistry or enzyme-linked immunosorbent assay (ELISA), respectively [ 42 , 43 ]. We observed that the HO-1 inducer, hemin, in the highest dose (10 mg/kg i.g.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This suggests that ZnPPIX counteracting protective effect of CORM-2 against ethanol ulcerogenesis cannot be explained by inhibitory effect of ZnPPIX on HO-1 enzyme expression and the mechanism of action of this compound in the stomach injured by ethanol should be further investigated. In contrast, ZnPPIX has been shown to afford protection against hemorrhagic lesions induced by cold restraint stress through reduction of free and total acidity of gastric secretion and decreased lipid peroxidation [ 45 ]. This apparent difference in the effect of ZnPPIX against cold stress- and ethanol-induced gastric damage could be attributed, at least in part, to the different experimental models of gastric injury depending (stress) and not depending (ethanol) upon gastric acid studied in their [ 45 ] and our present study.…”
Section: Discussionmentioning
confidence: 99%
“…It was also found that the process of endogenous antioxidant/Phase II detoxification was initiated to protect against cellular and tissue injury, as evidenced by the expression of heme oxygenase-1 (HO-1) in liver and kidney tissues. In previous studies, the rats subjected to restraint stress for 3 h exhibited a significant increase in HO-1 expression in stomach [47] and the exposure of acute restraint stress for 6 h caused Nrf2 and HO-1 in rat's hippocampus remarkably increased [48].…”
Section: Discussionmentioning
confidence: 88%